GRAFTING ON GUAR GUM - ITS DERIVATIVES: AN OVERVIEW - SUDHIR G. WARKAR,; A. P. GUPTA, (International Journal of Pharma and Bio Sciences, 2015)
Guar gum, a naturally occurring polysaccharide, is being widely used in graft copolymerization with vinyl monomers. In the present article, an attempt has been made in reviewing the literature based on guar gum, particularly related to its derivatization and graft copolymerization. This article exhaustively reviewed the efforts of various workers in the field of graft copolymerization of Guar gum and its various derivatives with various vinyl monomers and the potential effect of process parameters on graft copolymerization. It has been noted from the literature that the extent of grafting is greatly influenced by the process parameters such as initiator, monomer and gum concentrations and also influenced by the reaction time and temperature up to certain limit beyond which it shows decreasing trend.